THE ROLE OF INFORMATION IN INFLUENCING PUBLIC ATTITUDES AND BEHAVIORS IN A GLOBAL PANDEMIC - Nasser Al-Suqri, Mohammed; Mattar Al Salmi, Jamal; Mohamed Al Shabibi, Ayida (Humanities & Social Sciences Reviews, 2021)
Purpose of the Study: This study aims to identify key insights from the emerging academic literature relating to the role of information during COVID-19, especially information obtained via social media, and to consider their implications for the authorities responsible for pandemic management. Methodology: The research is based on a thematic review of 34 academic papers published during the first six months of 2020 when COVID-19 was spreading globally. Main Findings: The findings demonstrate the critical influence of information as an influence on public attitudes and behaviors in a pandemic, and the important role played by social media in the dissemination of information in this context. They highlight the problem of vast volumes of misinformation and fake news circulating on social media sites and how this can undermine efforts by the authorities to manage the pandemic. Social Implications: The research findings demonstrate the need for the authorities to utilize social media to counterbalance misinformation and fake news regarding the pandemic, but also highlight the importance of employing a range of information channels and messaging formats to effectively reach and engage all demographic groups. They suggest that key influencers including healthcare experts, high profile public figures, and social media influencers can play an important role in the dissemination of accurate and reliable information on behalf of the authorities in ways that support rather than hinder pandemic management. Originality/Novelty of the Study: Global pandemics have historically occurred only rarely and this is the first to occur in a new information environment in which people receive much of their information via the Internet and social media. A considerable number of academic papers relevant to this study were published in the first half of 2020, providing an early and unique opportunity to synthesize the key themes and findings and provide helpful insights on the use of social media and other information channels for pandemic management.